Bulk Ni–W alloys with a composite-like microstructure processed by spark plasma sintering: Microstructure and mechanical properties. (5th January 2016) - Sadat, T.; Dirras, G.; Tingaud, D.; Ota, M.; Chauveau, T.; Faurie, D.; Vajpai, S.; Ameyama, K.
Abstract: Spark plasma sintering was used to process Ni–W alloys from blends of Ni and W powders. The W amount ranged from 10 to 65 wt.%. XRD and EBSD investigations revealed the formation of Ni(W) solid solution along with clusters of pure W and remote quantities of WC or Ni6 W6 C carbide phases, depending on the initial W amount. The mechanical properties were investigated by tensile and hardness tests and compared to bulk Ni counterpart. Increasing the amount of W resulted in a grain size decrease of the Ni(W) component, probably due to grain boundary pinning by W solute atoms. This was also accompanied by an increase of both hardness and strength but at the expense of plastic strain. SEM investigations of the composite-like microstructures showed brittle fracture of the W clusters, whereas the Ni(W) solid solution counterpart exhibited a ductile behavior. Amongst the processed materials, the alloy containing an initial W amount of 30 wt.% exhibited the best combination of strength and uniform strain ( 800 MPa and 30%, respectively), which can be related to a cocktail-like effect coming from various strengthening sources, such as solid solution grain size reduction of the Ni(W), which also displayed a high number of Σ3 boundaries. Graphical abstract: Highlights: Bulk Ni–W alloys are designed by SPS of high purity Ni and W powder blends. Composite microstructures of W clusters + Ni(W) solid solution were obtained. Increasing the W amount results in the increase of both hardness and strength. The optimized alloy possesses a tensile strength of 805 MPa and a ductility of 41%.